The relationship of Gross Domestic Product, inflation and corruption to Foreign Direct Investment in selected Asean countries / Norhafizah Nazarudin - Nazarudin, Norhafizah (Faculty of Business and Management, 2015)
The aim of this study is to investigate the relationship of Gross Domestic Product, inflation, and corruption to the Foreign Direct Investment in five selected ASEAN countries which are Malaysia, Singapore, Thailand, Indonesia and Philippines. The study has used Panel Regression Model in order to discover the relationship between Gross Domestic Product, inflation, corruption and Foreign Direct Investment. The annual percentage of each variable starting from 2005 until 2014 is gathered in order to run test in this study. Based on the result, only gross domestic product has a significant positive relationship towards Foreign Direct Investment in five ASEAN countries Malaysia, Singapore, Thailand, Indonesia, and Philippines. It is shows that, the changes in Gross Domestic Product will make changes in Foreign Direct Investment. These results will make foreign investor and speculators to become more understand about the relationship of Gross Domestic Product, inflation and corruption to the Foreign Direct Investment.